Knowledge and practices towards hand hygiene among pediatric nurses in Hospital Universiti Sains Malaysia - Rani, Siti Nurshafiqiah Khazini Mohd (Universiti Sains Malaysia, 2016)
The most important factor in the prevention and control of nocosomial infections is with appropriate hand hygiene practice by healthcare workers. Knowledge and practices towards hand hygiene is essential in order to enhance the prevention or reduction of health care associated infections. The objective of this descritive and crosssectional study was to identify knowledge and practices towards hand hygiene among pediatric nurses in Hospital USM. A total of 66 respondents were selected using purposive sampling method. The data was obtained using a self-administered questionnaire which consisted of three sections. In section A there were five demographic characteristics, in section B and C there were nine with a 5-Likert type questionnaires in each to determine respondents’ level of knowledge and practices on hand hygiene. The data were processed with SPSS version 22.0 to analyze descriptive statistics, Chi Square test and Spearman rho’s correlation for answering the research questions. This study showed that respondents’ had excellent level of knowledge (70% excellent and 30% good knowledge level) and excellent practice level of hand hygiene (70% excellent and 30% good practice level). However, there was no significant relationship between socio-demographic variables and knowledge level (p>0.01) towards hand hygiene. But there was a significant correlation between knowledge and practices (r =1.000, p< 0.01). This showed that there was positive relationship between the respondents’ knowledge and practices whereby higher knowledge associated with excellent practices of hand hygiene. Overall, the findings of this study revealed that nurses must have good knowledge and practice level to sustain good hand hygiene to prevent cross infections in wards.